Mathematics Critical Thinking Skills Reviewed by Cognitive Styles and IQ on Discovery Learning with SPUR Approach - Riyadhotul Janah, Siti; Suyitno, Hardi; Rosyida, Isnaini (Unnes Journal of Mathematics Education Research, 2021)
The role of mathematics is to prepare students facing fast - growing challenges of 21st century. The required competence to master is such as critical thinking skill. This research aims to find out mathematics critical thinking skill pattern reviewed by cognitive styles and IQ on Discovery Learning with SPUR approach. This mixed method research used sequential explanatory. The population of this research consisted of seventh graders of Junior High School 2 Demak in academic year 2018/2019. The technique of sampling is purposive sampling based on cognitive styles and IQ of seventh graders from A class at Junior High School 2 Demak. The findings showed that mathematics critical thinking skills of students of categories, such as reflective, impulsive, slow and inaccurate, quick and accurate with normal, beyond normal and brilliant IQ levels showed various results. It was found reflective - impulsive, slow and inaccurate, quick and accurate with normal, beyond normal, and brilliant IQ levels whom in interpreting, analyzing, evaluating, and concluding did it very excellently, excellently, sufficiently excellent, and insufficiently. Thus, teacher must consider students’ cognitive styles in learning mathematics because there are several discrepancies of students’ problem solving ways.